D-step ahead Kalman predictor for controlled autoregressive processes with random coefficients - Hilgert, Nadine; Vila, Jean-Paul (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with prediction of controlled autoregressive processes with additive white Gaussian noise and random coefficients adapted to an observation process. Our aim is twofold. We begin by extending to the standard Kalman predictor a result of Chen et al. (1989) on the optimality of the "standard Kalman filter" when applied to linear stochastic processes with almost surely finite random coefficients.
Keywords: autoregressive processes; Kalman predictor; Kalman filters; extended Kalman filter